Osama the Hero (2004) de Dennis Kelly ou pourquoi le théâtre politique n’est pas une « foutue perte de temps » - Aloysia Rousseau (Sillages Critiques)
This article examines the relationship between theatre and politics based on two texts – one theoretical, the other fictional – by British playwright Dennis Kelly. It throws light on the way the Iraq War is approached in his 2004 play Osama the Hero as well as on the effects produced on the audience. Even though Kelly seems to minimize the political impact of his play in his opening speech for the Stückemarkt in Berlin in May 2012, entitled “Why political theatre is a complete fucking waste of time”, the play can indeed be deemed political, even if not obviously so. The notion of indignation will be scrutinized while the spectator’s stance will be defined as political because self-reflexive, the latter being invited to question his own convictions.